Development of a Prototype System for Monitoring and Controlling Apple Cider Vinegar Fermentation Using IoT-Based Fuzzy Methods - Hannisa Kautsarani Hamidah; Agus Khumaidi; Ii Munadhif; Ryan Yudha Adhitya (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
The apple cider vinegar fermentation process requires careful monitoring and control of variables such as pH, alcohol content, and amount of acetic acid. This research adopts Fuzzy Logic Control by utilizing the MQTT communication protocol, pH, alcohol and water pump sensors, as well as solenoid valves and DC motors as actuators. This Internet of Things (IoT) based solution provides real-time monitoring information on the fermentation process. The results showed that the test system succeeded in maintaining a stable pH of around 3.9-4.0 during the initial stages of fermentation, while industrial data showed greater variations. Alcohol content increased consistently in the test system, in contrast to the spike on day 7 in industry data. At the formulation stage, the pH dropped to 3.68 in the test system, while the industry maintained 3.70. At medium and slow mixing stages, the test system showed a significant decrease in pH and a consistent increase in alcohol. At the harvest stage, the pH was lower in the test system compared to industrial, with slightly higher alcohol content. Test results show that the implementation of this system can reduce the fermentation process time by up to 2 days faster compared to conventional methods. This conclusion shows that IoT-based systems are able to provide better control and monitoring than conventional systems, so they have great potential for wider adoption in the apple vinegar fermentation industry to increase production effectiveness.